Familiar Edible Flowers in Indonesia - I Nyoman Bagus Aji Kresnapati; Muhammad Eka Putra Ramandha; Nurul Indriani (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2022)
Flowers besides being used as ornamental plants, they can also be consumed. Flowers that can be consumed are called Edible Flowers. Edible flowers in general can be consumed directly, usually in tea or can be served in the form of processed food. Edible flowers contain phytochemical compounds such as anthocyanins, flavonoids, phenolics, carotenoids which are useful as antioxidants. Indonesia is rich in biodiversity with a variety of plant species that can grow, including edible flowers. There is diversity, but only a few edibles that can grow and are familiar to Indonesian people will be reviewed in this article.